Customised vestibular rehabilitation with the addition of virtual reality based therapy in the management of persistent postural-perceptual dizziness. Issue 10 (10th October 2021) - Mempouo, E; Lau, K; Green, F; Bowes, C; Ray, J
Abstract: Objective: Visual-vestibular mismatch patients experience persistent postural and perceptual dizziness. Previous studies have shown the benefit of vestibular rehabilitation for visual desensitisation using gaze stabilisation exercises and optokinetic stimulation. This study assessed the benefit of customised vestibular rehabilitation with visual desensitisation and virtual reality based therapy rehabilitation in the management of patients with persistent postural-perceptual dizziness. Methods: This retrospective study included 100 patients with Situational Characteristic Questionnaire scores of more than 0.9. All patients received virtual reality based therapy along with usual vestibular rehabilitation using gaze stabilisation exercises with a plain background followed by graded visual stimulation and optokinetic digital video disc stimulation. Patients' symptoms were assessed before and after vestibular rehabilitation using the Situational Characteristic Questionnaire, Generalised Anxiety Disorder Assessment-7, Nijmegen Questionnaire and Dizziness Handicap Inventory. Results: There were statistically significant improvements in Situational Characteristic Questionnaire scores, Nijmegen Questionnaire scores and Dizziness Handicap Inventory total score. However, there was a statistically insignificant difference in Generalised Anxiety Disorder Assessment-7 scores. There was a significant positive correlation between post-rehabilitation Situational Characteristic Questionnaire scores and other questionnaire results. Conclusion: Incorporating virtual reality based therapy with customised vestibular rehabilitation exercises results in significant improvement in persistent postural-perceptual dizziness related symptoms.